2009
DOI: 10.1002/jcb.22190
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major TG4 cross‐linking sites in the androgen‐dependent SVS I exclusively expressed in mouse seminal vesicle

Abstract: SVS I was exclusively expressed in seminal vesicle in which the protein was immunolocalized primarily to the luminal epithelium of mucosal folds. The developmental profile of its mRNA expression was shown to be androgen-dependent, manifesting a positive correlation with the animal's maturation. There are 43 glutamine and 43 lysine residues in one molecule of SVS I, which is one of the seven major monomer proteins tentatively assigned on reducing SDS-PAGE during the resolution of mouse seminal vesicle secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A male's ejaculate coagulates to form a copulatory plug inside the female reproductive tract in many different taxa, including nematodes (Abele & Gilchrist, ; Barker, ; Palopoli et al ., ), arachnids (Austad, ; Masumoto, ; Uhl et al ., ), insects (Parker, ; Dickinson & Rutowski, ; Orr & Rutowski, ; Rogers et al ., ), reptiles (Devine, ; Herman, ; Friesen et al ., ) and mammals (Devine, ; Martan & Shepherd, ; Voss, ; Williams‐Ashman, ; Dixson & Anderson, ). In rodents, this coagulation occurs when a prostate‐derived transglutaminase, encoded by the gene transglutaminase IV ( Tgm4 ), cross‐links seminal vesicle‐derived secretions upon mixing in the female's reproductive tract (Notides & Williams‐Ashman, ; Williams‐Ashman et al ., ; Fawell & Higgins, ; Esposito et al ., ; Lundwall, ; Lundwall et al ., ; Lin et al ., ; Tseng et al ., , ; Dean, ; Kawano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A male's ejaculate coagulates to form a copulatory plug inside the female reproductive tract in many different taxa, including nematodes (Abele & Gilchrist, ; Barker, ; Palopoli et al ., ), arachnids (Austad, ; Masumoto, ; Uhl et al ., ), insects (Parker, ; Dickinson & Rutowski, ; Orr & Rutowski, ; Rogers et al ., ), reptiles (Devine, ; Herman, ; Friesen et al ., ) and mammals (Devine, ; Martan & Shepherd, ; Voss, ; Williams‐Ashman, ; Dixson & Anderson, ). In rodents, this coagulation occurs when a prostate‐derived transglutaminase, encoded by the gene transglutaminase IV ( Tgm4 ), cross‐links seminal vesicle‐derived secretions upon mixing in the female's reproductive tract (Notides & Williams‐Ashman, ; Williams‐Ashman et al ., ; Fawell & Higgins, ; Esposito et al ., ; Lundwall, ; Lundwall et al ., ; Lin et al ., ; Tseng et al ., , ; Dean, ; Kawano et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found this peptide sequence in SVS2, but the sequence is not conserved in PATE4 (Supplemental Figure S3B). SVS1 also does not contain the sequence “QXK(S/T)”, but Tseng et al showed that two glutamine residues in SVS1 were the major site for TGM4 crosslinking by mass spectrometry (Supplemental Figure S3A) [8]. As PATE4 also has four glutamine and ten lysine residues (Supplemental Figure S3), our results suggest that PATE4 may have an unidentified target sequence for TGM4 or a function to promote plug formation independent from TGM4.…”
Section: Discussionmentioning
confidence: 77%
“…Although SVS1 does not contain the sequence “QXK(S/T),” Tseng et al . showed that two glutamine residues in SVS1 (Q 232 and Q 254 ) were the major site for TGM4 cross‐linking by mass spectrometry . Recently, we reported that prostate and testis expression 4 (PATE4; also known as SVS7) is the essential factor for copulatory plug formation with Pate4 KO mice (Figure and Table ) .…”
Section: Physiological Functions Of Accessory Gland Secretionsmentioning
confidence: 95%
“…In copulatory plug formation, it is thought that transglutaminase 4 (TGM4) from prostates and coagulating glands catalyze the formation of ε‐(γ‐glutamyl)lysine cross‐bridges among seminal vesicle secretion 1 (SVS1) to SVS3 (Table ) . In fact, previous papers showed that single KO males of Tgm4 or Svs2 are subfertile due to plug formation defects .…”
Section: Physiological Functions Of Accessory Gland Secretionsmentioning
confidence: 99%